The Relationship of Market Competition Intensity, Adoption of Financial and Non-financial Performance Measures to Company Performance - Puspita , Deta; Rahayu, Sri; Arum, Enggar Diah Puspa; Wiralestari, Wiralestari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the relationship between market competition intensity, adoption of financial and non-financial performance measures and company performance. The study was conducted at a manufacturing company in Batam. The variables in the study consist of independent and dependent variables. The independent variables are market competition intensity, financial and non-financial performance measures. The dependent variable is company performance. Data were collected using purposive random sampling method. The analysis method uses factor analysis (path analysis). The study resulted in market competition intensity having a positive relationship with company performance and was supported by previous research. Financial and non-financial performance had a positive relationship with company performance and was supported by previous research. The results of this study strengthen that market competition intensity has a positive relationship with company performance and the adoption of financial and non-financial performance measures has a positive relationship with company performance.